Sphingolipids and neuronal degeneration in lysosomal storage disorders. Issue 5 (16th August 2018) - Grassi, Sara; Chiricozzi, Elena; Mauri, Laura; Sonnino, Sandro; Prinetti, Alessandro
Abstract: Ceramide, sphingomyelin, and glycosphingolipids (both neutral and acidic) are characterized by the presence in the lipid moiety of an aliphatic base known as sphingosine. Altogether, they are called sphingolipids and are particularly abundant in neuronal plasma membranes, where, via interactions with the other membrane lipids and membrane proteins, they play a specific role in modulating the cell signaling processes. The metabolic pathways determining the plasma membrane sphingolipid composition are thus the key point for functional changes of the cell properties. Unnatural changes of the neuronal properties are observed in sphingolipidoses, lysosomal storage diseases occurring when a lysosomal sphingolipid hydrolase is not working, leading to the accumulation of the substrate and to its distribution to all the cell membranes interacting with lysosomes. Moreover, secondary accumulation of sphingolipids is a common trait of other lysosomal storage diseases. This article is part of the Special Issue "Lysosomal Storage Disorders" . Abstract : In this review article, we report on the sphingolipid chemical and biochemical properties and discuss some hypotheses about the possible links between sphingolipid incorrect catabolism and neurodegeneration. This article is part of the Special Issue "Lysosomal Storage Disorders" .